Efficacy and tolerability of bortezomib and dexamethasone in newly diagnosed multiple myeloma - Hassan Zafar, Mir Sadaqat; Khan, Afaq Ahmed; Aggarwal, Shyam; Bhargava, Manorama (South Asian Journal of Cancer, 2018)
Background: Outcome in multiple myeloma (MM) has improved substantially over recent years as a result of the availability of multiple novel agents with acceptable safety profile. Study Design: Prospective observational study at a tertiary care institute. Methods: Twenty-five newly diagnosed patients of MM were treated with bortezomib and dexamethasone induction with monitoring for response and safety, followed by peripheral blood autologous stem cell transplant (PBASCT) in eligible patients or maintenance. Results: Out of 25 patients, 32% attained complete response (CR), 56% very good partial response (VGPR), 4% PR, and 8% showed no response. The overall response rate was 92%. In our study, 56% of patients showed hematological side effects, out of which thrombocytopenia was seen in 32%, anemia in 16%, and leukopenia in 8%. Six patients developed bortezomib-induced peripheral neuropathy, out of which four had grade 1 (66.66%), one had grade 2 (16.66%), and 1 (16.66%) had grade 3 toxicity. Sixteen patients were eligible for PBASCT, out of which eight patients received this therapy while as remaining eight patients opted for two more cycles of induction therapy followed by maintenance. After completing 18 months of maintenance, all the eight patients who underwent PBASCT were in CR. Out of the 15 patients who did not receive PBASCT five attained CR, eight VGPR while as two patients relapsed. Conclusion: Bortezomib plus dexamethasone is highly effective and well-tolerated regimen for frontline treatment of MM with a higher quality of response in an advanced stage and renal failure patients.
Keywords: Bortezomib and dexamethasone; multiple myeloma; response rate